Investigation of calculations’ productivity at solving the aerodynamic problems in dis-tributed computing environment - Глазок, О. М. (Problems of Informatization and Management, 2010)
Research of calculable efficiency of processes of numeral solution of the systems of linear algebraic equations of large dimension, produced by aerodynamic problems, in distributed computing environment, is conducted. Efficiency of calculations at different conditions of organization of calculations is compared